A Review Paper On Detection And Control Of Hypertension Using Brain Wave Sensor - Praveen Sindagi, Dr. Mahesh P. K. (International Journal of Advanced Science and Technology, 2020)
High blood pressure (High BP) is known as hypertension in medical terms, which is caused due to too much pressure inside the blood vessels. As soon as heart drives it directs blood contiguous to ramparts of veins by potency cause stress. The added blood driven by heart and thinner arteries, caused the High blood-pressure. The present paper deals about different existing methodologies and researches made for detection and analysis of hypertension without any physical medication. The paper also aims at analyzing the good outcomes and overcoming the barriers faced by the different methodologies and surveys. Here we have analyzed different approaches with the first method deals Hybrid Wavelet method and K-means cluster method. The second approaches with neuro-fuzzy and adaptive fuzzy logic, while the third paper focus on mining class association with multiple features. The last methodology is based on ANN based information gain algorithm for diagnosis of hypertension. The paper concludes by digging up the major advantages off all the methodologies and exposers to an effective and best method.